Sheikh Waliyullah al-Dahlawi and his 'Kitab Hujjatul al-Baligah' and Muhammad Affandi Hassan and his theory of 'Gagasan Persuratan Baru': a brief study of the concept of Islamic literature - Yaacob, Adli; Kassim, Siti Nadhirah (IIUM Press, 2015)
Hujjat Al Baligha, undoubtedly, is one of the masterpieces written by Sheikh Waliyullah Al Dahlawi. It ‘scientifically„ emphasizes studies on society and its ethics/morals – branches of knowledge considered to be among the secrets of the sacred religion. This book appeared into two parts. The first explains the secrets of prophetic sunnah related to the well-being of sins and good deeds. To emphasize these aspects, the author referred to two general principles; firstly the aspect of good deeds and sins whilst the second deals with methods to unify existing religions. (Hermansen, 2000)